Sulfate-reducing bacteria and methanogens are involved in arsenic methylation and demethylation in paddy soils - Chen, Chuan; Li, Lingyan; Huang, Ke; Zhang, Jun; Xie, Wan-Ying; Lu, Yahai; Dong, Xiuzhu; Zhao, Fang-Jie (The ISME Journal, 2019)
Microbial arsenic (As) methylation and demethylation are important components of the As biogeochemical cycle. Arsenic methylation is enhanced under flooded conditions in paddy soils, producing mainly phytotoxic dimethylarsenate (DMAs) that can cause rice straighthead disease, a physiological disorder occurring widely in some rice growing regions. The key microbial groups responsible for As methylation and demethylation in paddy soils are unknown. Three paddy soils were incubated under flooded conditions. DMAs initially accumulated in the soil porewater, followed by a rapid disappearance coinciding with the production of methane. The soil from a rice straighthead disease paddy field produced a much larger amount of DMAs than the other two soils. Using metabolic inhibition, quantification of functional gene transcripts, microbial enrichment cultures and 13 C-labeled DMAs, we show that sulfate-reducing bacteria (SRB) and methanogenic archaea are involved in As methylation and demethylation, respectively, controlling the dynamics of DMAs in paddy soils. We present a model of As biogeochemical cycle in paddy soils, linking the dynamics of changing soil redox potential with arsenite mobilization, arsenite methylation and subsequent demethylation driven by different microbial groups. The model provides a basis for controlling DMAs accumulation and incidence of straighthead disease in rice.